Characteristic Oral Lesions of Syphilis Found in Three Stomatology Services in Latin America (Revista Nacional de Odontología, 2017)
Introduction: Syphilis is an ancient disease that has caused great damage throughout the history ofhumanity and, despite sexual protection methods and antibiotics to combat this infection, its prevalen-ce is still alarming today. The dentist plays an essential role in this field because he must be trained toearly detect the manifestations of the disease in the oral cavity, which would prevent its progression. Materials and methods: A cross-sectional, descriptive study was conducted, with 20 patients whoconsulted three stomatology services in South America; a stomatological examination was done and anexhaustive clinical history was obtained; the lesions found were classified and the other data collectedwere analyzed. Results: The lesion prevalent in primary syphilis was ulcers and only one case was detected; about thesecondary form, nineteen cases were detected, and multiple associated lesions were found; finally, nocase of tertiary syphilis was found. Conclusions: Disclosure of these results and further research in this field are considered essential toeducate and thus prevent the progression of syphilis to a latent or tertiary form that endangers the lifeof the population.
Keywords: sexually transmitted diseases; mouth neoplasms; serodiagnosis of syphilis; syphilis